2018
DOI: 10.1111/pace.13321
|View full text |Cite
|
Sign up to set email alerts
|

Nonfluoroscopic catheter ablation of paroxysmal atrial fibrillation

Abstract: Nonfluoroscopic ICE-guided catheter ablation of AF without prior cardiac image integration or angiography is feasible and safe. PVI without fluoroscopy did not affect procedure duration or long-term efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 19 publications
2
49
0
1
Order By: Relevance
“…The significant reduction in fluoroscopy time demonstrated in the main analysis was robust in all sensitivity testing, including studies with only AF patients (Hedges' g −1.25; 95% CI −2.14 to −0.36; P < .01) 10,11,24,26–31,37,38 . (Table S3).…”
Section: Resultsmentioning
confidence: 78%
See 4 more Smart Citations
“…The significant reduction in fluoroscopy time demonstrated in the main analysis was robust in all sensitivity testing, including studies with only AF patients (Hedges' g −1.25; 95% CI −2.14 to −0.36; P < .01) 10,11,24,26–31,37,38 . (Table S3).…”
Section: Resultsmentioning
confidence: 78%
“…Ten studies reported fluoroscopy dose data, with significant heterogeneity among studies (I 2 = 93%) and no evidence of publication bias or small study effects 23–28,31,33,37,38 . Use of ICE in ablation procedures showed significant reductions in fluoroscopy dose vs ablation without the use of ICE (Hedges' g −1.27; 95% CI −1.91 to −0.62; P < .01) (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations